Evaluation of Medical Intern\'s Competence Based on Objective Structured Clinical Examination (OSCE) in Babol Medical University of Sciences - Zhra Rezapour (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: The goal of clinical training in Medical education is achievement the minimum skills expected of medical graduates. In order to educate capable, responsible and responsive to community needs graduates, in addition to clinical course examinations & assessments it seems necessary to asses of clinical competence at the end of the internship. The aim of this study was to Evaluate Medical Intern's Competence Based on Objective Structured Clinical Examination (OSCE) in Babol Medical University of Sciences in 2016. METHODS: This Cross-sectional study was conducted on 28 of senior students of Babol University of Medical Sciences to evaluate their clinical competence in 2016. The test includes 15 stations (8 Question was essential and 5 questions was nonessential) that was designed based on the instructions of the Ministry of Health & Medical and Education. The test's reliability and validity was determined by the expert panel. Data were analyzed using SPSS software (version 21) and using descriptive and analytic statistics and independent t-test, paired t-test, Pearson coefficient. P<0.05 was considered significant. FINDINGS: the acquired mean score by participants was 15.81±0.93. The Students has been achieved the highest mean score in both eyes (20) and internal diseases (19.07±1.01) stations. They received the lowest mean score in gynecology station (11.68± 2.9). More than 50% of students had been in the poor to moderate rang Neurological & health stations. Pearson correlation coefficient showed significant relationship between the mean score & the average score of students before the pre-internship course. (p<0.05)(r= 0.49), while this test showed no significant relationship between mean score and age (P> 0.05). T-test showed significant relationship between in two group's essential & non-essential station. (p<0.05) CONCLUSION: According to acquired scores in neurology, Health & gynecology stations that has been in the poor to moderate rang, attention to educational facilities such as holding clinical educational workshops, further use of the Clinical Skills Lab as well as taking advantage of educational videos and practice under supervision seems to be necessary to achieve educational goals